CORRELATION BETWEEN NUTRITIONAL STATUS AND SIMPLE FEBRILE SEIZURE IN CHILDREN AGED 6 MONTHS – 5 YEARS AT PHC HOSPITAL SURABAYA - Wibowo, Felinda Chandra; Liona Dewi, Dewa Ayu; Sudewi, Ni Putu (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Around 2 – 3% of children in Indonesia experience febrile seizures. Factors that can increase the risk of febrile seizures is viral infection and nutritional status. Malnourished in children increase the incidence of febrile seizures in children.Objective: To analyze the relationship between nutritional status and simple febrile seizures in children aged 6 months to 5 years at PHC Hospital in Surabaya.Method: The study utilized a retrospective observational analytical design with a case control research method on inpatients with fever at PHC Hospital in Surabaya from January 2019 to September 2023, involving a total of 2,464 patients. Data were extracted from medical records and selected based on inclusion and exclusion criteria, resulting in 105 samples in the case group and 758 samples in the control group, meeting the inclusion and exclusion criteria. Thirty-seven samples were randomly selected from each group using simple random sampling. Statistical analysis employed the C contingency coefficient test.Results: Among patients with simple febrile seizures at PHC Hospital in Surabaya, 8,1% were severe thinness, 29,8% were thinness, 48,6% had normal, 8,1% were at risk of overweight, 2,7% were overweight, and 2,7% were obese. The fever without seizures group showed no severe thinness, 5,4% were thinness, 86,5% had normal, 2,7% were at risk of overweight, 5,4% were overweight, and no obese. Based on the statistical analysis using the C contingency coefficient test, the p-value was 0,008 (p<0,05), indicating a correlation between nutritional status and simple febrile seizures in children aged 6 months to 5 years at PHC Hospital in Surabaya.Conclusion: There is a correlation between nutritional status and simple febrile seizures in children aged 6 months to 5 years at PHC Hospital in Surabaya.